2020
DOI: 10.1038/s41380-020-00885-2
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal air pollution influences neurodevelopment and behavior in autism spectrum disorder by modulating mitochondrial physiology

Abstract: We investigate the role of the mitochondrion, an organelle highly sensitive to environmental agents, in the influence of prenatal air pollution exposure on neurodevelopment and behavior in 96 children with autism spectrum disorder (ASD) [45 with neurodevelopmental regression (NDR); 76% Male; mean (SD) age 10 y 9 m (3 y 9 m)]. Mitochondrial function was assessed using the Seahorse XFe96 in fresh peripheral blood mononuclear cells. Second and third trimester average and maximal daily exposure to fine air particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 92 publications
(154 reference statements)
3
36
0
Order By: Relevance
“…The prenatal Cu to Zn ratio was associated with two independent measures of language development in all children with ASD (both those with and without NDR) [ 29 ]. This latter study extends previous findings linking prenatal nutrient metal (Zn, Mn, Cu) exposure and ASD [ 26 , 27 , 124 , 125 , 126 , 127 ].…”
Section: Unique Asd Mitochondrial Abnormalities May Be Linked To Bsupporting
confidence: 89%
See 2 more Smart Citations
“…The prenatal Cu to Zn ratio was associated with two independent measures of language development in all children with ASD (both those with and without NDR) [ 29 ]. This latter study extends previous findings linking prenatal nutrient metal (Zn, Mn, Cu) exposure and ASD [ 26 , 27 , 124 , 125 , 126 , 127 ].…”
Section: Unique Asd Mitochondrial Abnormalities May Be Linked To Bsupporting
confidence: 89%
“…Abnormalities in several nutrient metals have been linked to an increased risk of ASD. Studies have associated an increased risk of ASD with atypical pre- and postnatal Zn and Cu metabolism [ 26 ] and found that atypical levels of essential (Zn, Mn) and non-essential (Pb) metals during prenatal development and early life in individuals with ASD are associated with long-term physiological and developmental alternations [ 27 ]. Studies have associated low maternal iron (Fe) with increased ASD risk [ 28 ].…”
Section: Prenatal Risk Factors For Asd Modulate Mitochondrial Funcmentioning
confidence: 99%
See 1 more Smart Citation
“…Reciprocally, the nucleus regulates the mitochondrion via an array of transcription factors ( 50 ). Hence, partial mitochondrial defects caused by hemizygous mutations, modulated by background mtDNA variation ( 25 ) and environmental challenge ( 51 , 52 ), could cause similar mitochondrial defects to that of the ND6 P25L mouse.…”
Section: Discussionmentioning
confidence: 99%
“…Air pollution including fine air particulate matter (PM) and gaseous pollutants is a crucial toxicant caused by human activities. Generally, air pollution exposure is related to lots of chronic diseases, such as pulmonary and cardiovascular disease [ 62 ]. To clean PM 2.5, Guo et al reported an SP triboelectric negative air ion generator (MSNG) powered by TENG [ 63 ].…”
Section: Applications Of Self-powered Electrochemical Systemmentioning
confidence: 99%